Comprehensive organ-specific radiation dose mapping in coronary angiography using the Alderson Rando phantom: An experimental approach to optimize patient safety - Kayaokay, Duygu Tuncman; Kesmezacar, Fahrettin Fatih; Yeyin, Nami; Karacam, Songul Cavdar; Gunay, Osman; Karabag, Turgut; Demir, Mustafa; Issa, Bashar; Tekin, H. O.; Almisned, Ghada (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study aimed to evaluate radiation dose distribution to critical organs, specifically the lungs, heart, and breasts, during coronary angiography using the Alderson Rando phantom. Thermoluminescent dosimeters (TLDs) were positioned at different anatomical sites within the Alderson Rando (R) phantom to measure radiation exposure in a controlled simulation replicating clinical coronary angiography conditions. Our findings indicated significant variability in lung doses, with the highest exposure observed in middle lung regions due to direct alignment with the primary X-ray beam path. Cardiac dose measurements showed a relatively uniform distribution, with elevated exposure in the basal and atrial regions, reflecting their proximity to the central beam. In the breast tissue, a pronounced dose asymmetry was noted, with the right breast, particularly lateral and posterior regions, receiving substantially higher radiation due to its closer positioning to the X-ray source and increased scatter. According to results, there are different levels of radiation exposure across organs and anatomical regions during coronary angiography. It can be concluded that implementing targeted dose-reduction strategies, such as shielding and optimized angulation, is essential to protect sensitive organs, with personalized imaging protocols recommended to enhance patient safety and minimize cumulative radiation risks.
Keywords: Alderson Rando phantom; Coronary angiography; Dose measurement; Radiology; Radiation risk assessment; COMPUTED-TOMOGRAPHY ANGIOGRAPHY; MONTE-CARLO-SIMULATION; CT ANGIOGRAPHY; REDUCTION; Chemistry; Nuclear Science & Technology; Physics